Green human resource management for organizational sustainability: lessons from insurance companies in emerging market - Chaudhary, Manoj Kumar; Chaudhary, Rajesh Kumar (Journal of Emerging Management Studies, 2023)
Purpose – This paper was intended to examine the effects of green HRM practices on organizational sustainability in Nepalese life insurance companies. The ongoing discourse on green HRM practice as a key organizational strategy for organizational sustainability has been paid attention of many researchers across the globe. Design/methodology/approach – In order to give a general overview of present scenario on implementation of green HRM practices and their connection to corporate sustainability, this research used a descriptive research design. For this, the study has gone through structured questionnaires to collect primary data from the sample of 190 officer-level employees across nine eldest life insurance companies in Nepal. Findings – This study found that Nepalese life insurance companies are in the early period of applying green HRM practices. However, the regression analysis demonstrated that emerging practices of green HRM has made significant positive contribution to organizational sustainability. The findings of this research depicted that sampled organizations have realized benefits of green HRM practices. This study concluded that the gap existed because of the lack of awareness towards handling the green issues in Nepalese context. Practical Implications – This study will be productive to make constructive decision for applying the approach of green HRM for long run existence of corporations. Yet, this paper has some uncovered areas of green HRM practices as to state best green HRM practices which contribute to achieve organizational sustainability in different backgrounds of emerging nations.